Egg parasitoids (Hymenoptera: Mymaridae and Trichogrammatidae) of the gall-making leafhopper Scenergates viridis (Hemiptera: Cicadellidae) from Uzbekistan, with taxonomic notes on the Palaearctic species of Aphelinoidea - Rakitov, Roman; Triapitsyn, Serguei V. (Zootaxa, 2013)
A new species of the Aphelinoidea Girault (Hymenoptera: Trichogrammatidae), A. (Aphelinoidea) sariq Triapitsyn & Rakitov sp. n., is described from Uzbekistan. Both sexes were reared from eggs of the only known truly gall-making leaf-hopper, Scenergates viridis (Vilbaste), laid inside its galls on camelthorn, Alhagi maurorum Medikus; additional females were found dead inside the galls. Aphelinoidea sariq is the only known species of the nominate subgenus of Aphelinoidea whose body color is predominantly yellow. Taxonomic notes on other Palaearctic species of Aphelinoidea are provided; A. scythica Fursov, syn. n. is synonymized under A. (Aphelinoidea) turanica S. Trjapitzin. Another trichogrammatid, Par-acentrobia (Paracentrobia) sp., was reared from eggs of S. viridis in much smaller numbers. Also described from the same locality and host is Gonatocerus (Lymaenon) mitjaevi Triapitsyn & Rakitov sp. n. (Hymenoptera: Mymaridae).